Association Between Admission-to-Surgery Time and Outcomes in Traumatic Brain Injury at RSSA - Yuddy Imowanto; Holipah; Sri Wahyuni (Saintika Medika : Jurnal Ilmu Kesehatan dan Kedokteran Keluarga, 2026)
Despite evidence that streamlined trauma protocols reduce preoperative delays and improve survival, delays from emergency department admission to surgical intervention remain common and are associated with poorer outcomes. Although international guidelines recommend decompression within a four-hour “golden period,” data on adherence in Indonesia remain limited. This retrospective cohort study evaluated 91 patients with traumatic brain injury (TBI) who underwent neurosurgical intervention at Saiful Anwar Hospital, Malang, between 2023 and 2024. The association between preoperative time intervals and clinical outcomes, including mortality, Glasgow Outcome Scale at hospital discharge (GOS-HD), and length of stay (LOS), was analyzed. Admission-to-surgery time was not significantly associated with mortality (p = 0.725) or GOS-HD (p = 0.648). However, prolonged total time to surgery (p = 0.029) and extended CT-to-surgery intervals (p = 0.026) were significantly associated with increased LOS. These findings indicate that while surgical delays may not directly affect short-term survival or functional outcomes, they contribute to longer hospitalization and reduced care efficiency. Efforts to minimize post-CT delays may improve workflow and optimize trauma care delivery.